80 million-twenty-foot-equivalent-unit container port? : sustainability issues in port and coastal development - Yap, Wei Yim (2013)
The container port industry has experienced phenomenal growth over the past decades since the era of containerisation. The continuous population growth, urbanisation and industrialisation will continue to propel seaborne commodity trades which are largely handled via ports. Given that the four busiest container ports of Shanghai, Singapore, Hong Kong and Shenzhen handle significantly high throughputs, this research aims to examine their likely growth paths, sustainability issues in port and coastal development and related policy implications. The paper uses a longitudinal approach to analyse growth patterns that are exhibited by the selected ports in 1990–2010. The results of which will be used to derive scenarios for throughput growth and additional quay length required up to 2025. Container ports could expect to face immense pressure for their traffic-handling systems given that container throughput is projected to increase by several times within the next 15 years. The research contributes to both policy and research by addressing the need for a balanced approach in sustainability for port and coastal development. Increasing capacity does not mean that ports must resort to new terminal/berth construction extensively. If the decision is made to accommodate this growth in throughput, innovative solutions and flexibility in capacity expansion will also be required to accommodate the addition to traffic given the scale involved so as to alleviate pressures on spatial demand and the environment.